Rate of Detection and Antibiotic Resistance Pathogens of Purulent-Septic Infections in Cardiac Surgery Patients - V I Sergevnin; L G Kudryavtseva; O G Pegyshina (Эпидемиология и вакцинопрофилактика)
Relevance. Among cardiac surgery hospital patients, purulent-septic infections (healthcare-associated infection or further HAI) do often occur. Aim of the work is to study the frequency of detection and antibiotic resistance of certain types of microorganisms in the development of HSI in operated patients of a cardiac surgery hospital. Materials and methods. The results of bacteriological examination of 213 operated patients with signs of HAI and 836 patients without signs of HAI were studied in a cardiac surgery hospital. The sensitivity of dominant microorganisms to antibiotics was determined. Results. Among patients operated in a cardiac surgery hospital Staphylcoccus epidermidis was more often extracted from the wound discharge, K. pneumoniae and fungi of the genus Candida were extracted from sputum, S. epidermidis and fungi of the genus Candida were extracted from blood, K. pneumoniae and Escherichia were extracted coli urine. These microorganisms were found among patients with signs of HAI significantly more often than among patients without signs of HAI. Among the dominant pathogens of HAI, a significant proportion of strains with multiple antibiotic resistance was identified, and among K. pneumoniae were found extremely resistant and pan-resistant clones producing extended-spectrum beta-lactamases. Conclusion. K. pneumoniae, S. epidermidis, E. coli and fungi of the genus Candida were the leading pathogens of HAI among patients operated in a cardiac surgery hospital. A significant number of bacterial strains with multiple antibiotic resistance have been identified.